Letter from Jesse M. Unruh - Jesse M. Unruh:::::: (1968)
This letter from the California Democratic Delegation, chaired by Jesse M. Unruh, urges delegates to support a coordinated slate of candidates for party leadership positions at meetings held August 10–11 in Sacramento. The authors argue that the Democratic Party faces serious political challenges in California, including narrow legislative margins and difficult statewide and presidential races. They promote endorsed candidates for Democratic National Committeeman and Committeewoman, as well as multiple state party offices, emphasizing unity, joint fundraising, and organizational cooperation. The letter stresses that revitalizing party operations is essential for achieving electoral victories both immediately and in the future. It is signed by numerous prominent Democratic leaders, including Alan Cranston, Philip Burton, George Moscone, and other state and national figures.